Integrated optomechanical analysis - Doyle, Keith B. (SPIE monograph, 2012)
The development of integrated optomechanical analysis tools has increased significantly over the past decade to address the ever-increasing challenges in optical system design, leveraging advances in computational capability. This book presents not only finite-element modeling techniques specific to optical systems but also methods to integrate the thermal and structural response quantities into the optical model for detailed performance predictions. This edition updates and expands the content in the original SPIE Tutorial Text to include new illustrations and examples, as well as chapters about structural dynamics, mechanical stress, superelements, and the integrated optomechanical analysis of a telescope and a lens assembly.